2018
DOI: 10.15407/microbiolj80.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Bradyrhizobium japonicum Strains in Soil at their Introduction into Soybean Agrocenosis

Abstract: Оцінити здатність штамів Bradyrhizobium japonicum з повільним та інтенсивним ростом приживатись у ґрунті та тривалий час зберігати симбіотичну активність. Методи. Приживаність штамів-інокулянтів у ґрунті вивчали у польових дослідах із соєю (Glycine max (L.) Merr.). Як рослини-пастки для ризобій сої використовували вигну китайську (Vigna unguiculata (L.) Walp.), маш (Vigna radiata (L.) Wilczek) та квасолю адзукі (Vigna angularis (Willd.) Ohwi & H.Ohashi). Наявність досліджуваних штамів у бульбочках визначали у … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The investigation of their biological properties showed that strains of soybean rhizobia with different growth rates have significant differences in phenotypic and genotype characteristics. It has been established that intensely grown strains actively colonize the roots of plants and are better settled down in the soil than slowly grown, that is, they are characterized by increased saprophytic competence [7]. This feature of the studied strains of nodule bacteria can be used in practice when creating new microbial preparations with a wide range of beneficial effects.…”
mentioning
confidence: 99%
“…The investigation of their biological properties showed that strains of soybean rhizobia with different growth rates have significant differences in phenotypic and genotype characteristics. It has been established that intensely grown strains actively colonize the roots of plants and are better settled down in the soil than slowly grown, that is, they are characterized by increased saprophytic competence [7]. This feature of the studied strains of nodule bacteria can be used in practice when creating new microbial preparations with a wide range of beneficial effects.…”
mentioning
confidence: 99%